Exploring English Teachers' Perceptions About Peer-Coaching as a Professional Development Activity of Knowledge Construction - Adriana Castañeda-Londoño (Asociación Colombiana de Profesores de Ingles, 2017)
Teachers' knowledge and how they construct it is an area that deserves attention when it comes to producing fruitful professional development practices. This small-scale action research aims at identifying the perceptions of three teachers in a private language center about peer-coaching and their actual construction of knowledge in a peer-coaching activity. Data were collected through two narratives and the transcription of recorded conversations among participants after the observation of their classes. The results suggest that before peer-coaching teachers held three types of perceptions towards observation and feedback: a cautious approach, an identity tension approach, and a celebratory approach. After peer-coaching one sees that two perceptions emerged: observation and feedback entail, on the one hand, high anxiety about teachers' self-image; and on the other, observation and feedback show a deep sense of their selves.